2020
DOI: 10.1039/d0ra06545e
|View full text |Cite
|
Sign up to set email alerts
|

AuNPs@PMo12nanozyme: highly oxidase mimetic activity for sensitive and specific colorimetric detection of acetaminophen

Abstract: The design of a highly specific and sensitive approach for the quantitative and qualitative determination of acetaminophen (AP) is crucial from a human health point of view.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…In addition, different TMB derivatives can be generated in the reaction medium, such as charge-transfer complexes and di-imines (di-cations because of double electron transfer). A blue charge-transfer complex with absorption peaks at 652 and 370 nm and a yellow di-imine derivative (460 nm) is formed by two-electron oxidation [17] , [105] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, different TMB derivatives can be generated in the reaction medium, such as charge-transfer complexes and di-imines (di-cations because of double electron transfer). A blue charge-transfer complex with absorption peaks at 652 and 370 nm and a yellow di-imine derivative (460 nm) is formed by two-electron oxidation [17] , [105] .…”
Section: Resultsmentioning
confidence: 99%
“…(1) Ag (I) ions present in the nanozyme solution (according to ICP analysis, 1 mM) cause TMB oxidation. This can be detected by absorption spectra (typical oxTMB peaks at 370 and 655 nm) and visually by blue color [17] . Hence, unreacted Ag + ions in the GO-Ag 2 O colloidal solution may play a role in oxidizing TMB to oxTMB and producing Ag (0) [108] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The above results indicated that the HRP&Au@ZIF-8/cDNA composites could maintain the catalytic activity of HRP. The enzymatic kinetic properties of the HRP&Au@ZIF-8/cDNA composites were analyzed according to the Michaelis-Menten model [36]. The apparent Michaelis-Menten constant (K m ) and the maximum reaction velocity (V max ) were determined to be 1.36 mM and 8.39 × 10 -2 mM/s, respectively, from the Lineweaver-Burk plot (Figure S5).…”
Section: Characterization Of the Hrpandau@zif-8 Compositesmentioning
confidence: 99%
“…(1) PMo 12 , a classical Keggin-type POM, has proven to be a good kind of enzymemimicking reagent. 26,27 (2) The diameter of PMo 12 is ca. 11 Å, being suitable for encapsulation into the inherent cavities of MIL-100(Fe).…”
Section: Introductionmentioning
confidence: 99%